2020
DOI: 10.1016/j.celrep.2020.108435
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Telomere and DNA Damage Responses in the Space Radiation Environment

Abstract: Highlights d Telomere elongation during spaceflight was observed for two 6-month mission astronauts d Telomere elongation was not dependent on mission duration, sample, or measurement type d Chronic space radiation exposure was associated with persistent DNA damage responses d Telomeres shortened rapidly after return to Earth, and longterm individual differences were observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 94 publications
1
36
0
Order By: Relevance
“…Repeat-rich, low-complexity regions of the human genome such as telomeres have been historically recalcitrant to full mapping and annotation (Miga 2015), mainly owing to the alignment challenge they pose and to the read lengths required to span such areas (Treangen and Salzberg 2012). The advent of long-read, single-molecule methods (third-generation sequencing) has provided new opportunities to map the sequence composition of a previously "dark" area of the human genome, enabling research into the sequence composition and length dynamics (Luxton et al 2020a(Luxton et al , 2020b of telomeres. Our results not only reaffirm that the canonical repeat (5 ′ -TTAGGG-3 ′ ) is certainly the most dominant motif found within telomeres but also reveal a range of diverse, noncanonical repeat variations, which are confirmed by both short-and long-read sequencing technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat-rich, low-complexity regions of the human genome such as telomeres have been historically recalcitrant to full mapping and annotation (Miga 2015), mainly owing to the alignment challenge they pose and to the read lengths required to span such areas (Treangen and Salzberg 2012). The advent of long-read, single-molecule methods (third-generation sequencing) has provided new opportunities to map the sequence composition of a previously "dark" area of the human genome, enabling research into the sequence composition and length dynamics (Luxton et al 2020a(Luxton et al , 2020b of telomeres. Our results not only reaffirm that the canonical repeat (5 ′ -TTAGGG-3 ′ ) is certainly the most dominant motif found within telomeres but also reveal a range of diverse, noncanonical repeat variations, which are confirmed by both short-and long-read sequencing technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown in astronaut leukocytes that long-duration spaceflights (6–12 months) lengthened telomeres, but that telomeres were rapidly shortened to a pre-spaceflight length within a few days after the astronauts returned to Earth [ 80 , 81 ]. The authors posited that these effects were caused by space radiation.…”
Section: Telomere Response To Stressmentioning
confidence: 99%
“…The combination of the two stressors can enhance detrimental effects of the space environment, particularly for long-duration missions, where a condition of chronic exposure exists. In this regard, studies derived from cell samples of cosmonauts and space-flown rats have shown an increase in oxidative stress, inflammation, lipid peroxidation, and a decrease of several blood antioxidants [ 4 , 41 , 42 ]. Alterations in the transcriptional profile of the human immune system were detected in cells such as macrophages and T cells when exposed to an altered gravitational environment [ 43 ].…”
Section: Oxidative Stress and Damage (Osad) Generation In The Space Environmentmentioning
confidence: 99%
“…Similarly, Overbay et al [ 44 ] found gene expression changes and oxidative damage in the retina of space-flown mice that remained aboard the ISS for 35 days. Persistence of DDR activation, including mitochondrial and oxidative stress, chromosomal aberrations, and telomere elongation has been observed in three unrelated astronauts employed for two 6-month spaceflight missions [ 4 , 42 ]. Loss of function or imbalance in DDR proteins leads to several human diseases including cancer, a risk for spaceflight members exposed to space radiation.…”
Section: Oxidative Stress and Damage (Osad) Generation In The Space Environmentmentioning
confidence: 99%
See 1 more Smart Citation